2019
DOI: 10.1093/jas/skz269
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid in the absence of a PPARγ agonist increases adipogenic gene expression in bovine muscle satellite cells1

Abstract: We hypothesized that oleic acid (OA) in the absence of a thiazolidinedione (i.e., a synthetic peroxisome proliferator-activated receptorγ [PPARγ] agonist) would increase adipogenic gene expression in bovine muscle satellite cells (BSC). The BSC were cultured in differentiation medium containing 10 µM ciglitazone (CI), 100 µM OA, or 100 µM OA plus 10 µM CI (CI-OA). Control (CON) BSC were cultured only in differentiation media (containing 2% horse serum). The presence of myogenin, desmin, and paired box 7 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…In this study, ciglitazone in the absence of an adipocyte differentiation cocktail also induced an up-regulation of adipogenic gene expression accompanied by low expression of MYOD. And the higher PLIN2 expression and adiponectin promotes the higher lipid droplets accumulation in the BSC [4]. The PI3K-Akt signaling pathway plays an important regulatory role in adipocyte differentiation and adipogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In this study, ciglitazone in the absence of an adipocyte differentiation cocktail also induced an up-regulation of adipogenic gene expression accompanied by low expression of MYOD. And the higher PLIN2 expression and adiponectin promotes the higher lipid droplets accumulation in the BSC [4]. The PI3K-Akt signaling pathway plays an important regulatory role in adipocyte differentiation and adipogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Teboul et al first reported the almost complete conversion of C2C12 myoblasts to lipid-filled cells when incubated with linoleic acid (18:2n-6) plus the TZD pioglitazone, as indicated by a cessation of myoblast fusion, swelling of myoblasts through lipid filling, down-regulation of myogenin (MYOG), and up-regulation of adipocyte lipid-binding protein gene expression [5]. In our previous study [4], we established that 10 µM ciglitizone down-regulated the expression of genes associated with myogenesis, and up-regulated genes involved in adipogenesis. However, we did not establish that 10 µM ciglitizone would elicit maximal effects on adipogenesis and/or myogenesis.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Computational approaches to media development are better suited for solving such multifactorial problems, and should therefore be leveraged to further optimize Beefy-9 and other serum-free media for cultured meat applications 27 . Here, efforts can focus on adipose as well as muscle tissue, for instance through the use of free fatty acid addition to Beefy-9 to induce the transdifferentiation of BSCs into lipid-accumulating cells 31 . Additionally, further work is needed to overcome the slower long-term growth and aberrant lipid accumulation that is seen in BSCs cultured over seven passages in Beefy-9.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that cells from myogenic cultures that have showed myogenic response could be transferred from this pathway when treated with bone-morphogenetic proteins or adipogenic-inducing agents (12,13). Our previous studies have shown that oleic acid, as the most abundant monounsaturated fatty acid in beef marbling, has the ability to differentiate microsatellite cells into adipocyte-like lipid droplets (14). However, it is not clear whether palmitoleic acid (POA), the second most abundant monounsaturated fatty acid in beef marbling, has the same characteristics as oleic acid.…”
Section: Introductionmentioning
confidence: 99%